2023
DOI: 10.3390/jox13030024
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis- and Substance-Related Carcinogenesis in Europe: A Lagged Causal Inferential Panel Regression Study

Abstract: Recent European data facilitate an epidemiological investigation of the controversial cannabis–cancer relationship. Of particular concern were prior findings associating high-dose cannabis use with reproductive problems and potential genetic impacts. Cancer incidence data age-standardised to the world population was obtained from the European Cancer Information System 2000–2020 and many European national cancer registries. Drug use data were obtained from the European Monitoring Centre for Drugs and Drug Addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 251 publications
0
6
0
Order By: Relevance
“…In the initial studies, tobacco smoking and alcohol were identified as cofactors. Recent research has identified significant associations between cannabis use and various malignant disorders, including oropharyngeal cancer [96]. Cannabis is a stronger carcinogen than tobacco or alcohol, with the concentration of the phytocannabinoid THC playing a key role [96].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the initial studies, tobacco smoking and alcohol were identified as cofactors. Recent research has identified significant associations between cannabis use and various malignant disorders, including oropharyngeal cancer [96]. Cannabis is a stronger carcinogen than tobacco or alcohol, with the concentration of the phytocannabinoid THC playing a key role [96].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified significant associations between cannabis use and various malignant disorders, including oropharyngeal cancer [96]. Cannabis is a stronger carcinogen than tobacco or alcohol, with the concentration of the phytocannabinoid THC playing a key role [96]. Other studies do not support a direct association or even suggest potential anti-cancer effects of cannabinoids in oral cancer [101,110,111].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unequivocal demonstration that cellular dedifferentiation occurs due to DNA demethylation, weakening of superenhancers and superanchors, aberrant promoter–enhancer communication, and retrotransposon activation clearly explains why many diverse tissues are primed by cannabis for malignant transformation, which addresses the issue of why so many cancers have been epidemiologically linked with cannabis ( 25 , 28 , 32 , 179 – 188 , 220 , 234 247 ). Cancers that were linked with cannabis exposure in Europe were all cancers, excluding non-melanoma skin cancer, bladder, brain, breast, colorectal, Hodgkin's, kidney, larynx, liver, lung, melanoma, multiple myeloma, myeloid and lymphoid leukemias, non-Hodgkin's lymphoma, and esophagus, oropharynx, ovary, pancreas, prostate, stomach, testis, thyroid, and uterine cervix cancers ( 189 ).…”
Section: Aging–epigenomic Agingmentioning
confidence: 99%
“…For these reasons, it is envisaged that the triple confluence of rising cannabis prevalence rates, intensity of use rates, and cannabinoid potency will manifest relatively abruptly as steep rises in adverse mental health, as well as teratologic, carcinogenic, and age-related outcomes, as are indeed being observed and documented in several jurisdictions ( 16 , 25 , 27 32 , 179 – 187 , 189 205 , 207 , 232 , 234 – 237 , 321 , 342 345 ).…”
Section: Epigenomicsmentioning
confidence: 99%